A comparison of Janus kinase inhibitor safety in rheumatoid arthritis. (15th June 2021) - Nash, Peter; Lim, Irwin; Marabani, Mona
Abstract: The last decade has seen considerable advancement in the treatment options available to patients with rheumatoid arthritis (RA) through the development of oral, small molecules that target and inhibit Janus kinases (JAKi). These drugs have a rapid onset of action, disrupting the Janus kinase/signal transducer and activator of transcription pathway and preventing the production of cytokines involved in inflammatory processes. They have the potential to provide immunomodulatory benefits across a broad range of diseases. This narrative review focuses on the safety profile of tofacitinib, baricitinib, upadacitinib, and filgotinib. Although JAKi have been shown to be effective in the treatment of RA, it is posited that they have different selectivities, which are likely to affect their safety profiles in RA patients. Currently, there are limited long‐term safety data available, with most data coming from randomized controlled trials. However, the data that are available show that upadacitinib and filgotinib may have improved safety profiles. This is particularly true in relation to herpes zoster, venous thromboembolism, and gastrointestinal perforation. Future research is needed to investigate the safety and efficacy of switching between JAKi when a previous JAKi has not been tolerated or has been ineffective.